Relasi Gender Pada Perkawinan Antar Etnis: Studi Kasus Perempuan Minangkabau - Rika Febriani; Susi Fitria Dewi (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
Gender relations on inter-ethnic marriage (Minangkabau Women's Case Study). Inter-ethnic marriage in Indonesia is a strategy in strengthening the integration of the nation in the modern era. Minangkabau as one of the big ethnicities is included on thissocial facts. One of the driving factors is merantau tradition. The culture of merantau allows Minangkabau people then interacts with various ethnicities and nations. Meanwhile, women in Minangkabau have a special role because they adhere to the matrilineal kinship system. They can carry out marriage with ethnicity and other tribes outside Minangkabau and maintain their traces at the same time. This cultural factor strengthens marriage patterns and affects the family formation process. The attitude of women in inter-ethnic marriage relations also plays a role in solving problems in the family. This paper discusses how Minangkabau women's strategy in inter-ethnic marriage relations in Indonesia? What factors affect Minangkabau women in choosing a partner who comes from outside the tribe? The research method used is qualitative by using the framework of the theory of feminism on the freedom and separation of the realm of Public and Private. Research uses Minangkabau women's samples who carry out marriage with the Batak, Java and Sundanese tribes that have been going on for more than ten years. The results of the study found that Minangkabau women could play an active and independent role in inter-ethnic marriage bonds. This attitude is in line with the views of feminism who emphasize freedom in choosing and acting, and the absence of separation between public and private spaces.